Experimental and theoretical study of penetration of spheroconical bodies into a sand target - Balandin, Vladimir Vasil'evich; Bragov, Anatoly Mikhailovich; Krylov, Sergey Valer'evich; Tsvetkova, Yelena Valer'evna (Computational Continuum Mechanics, 2010)
The results of direct and reverse normal impact laboratory experiments performed to study spheroconical bodies with barriers of sand filled in metal cylindrical containers are given. The data are compared with the numerical simulation results obtained based on the modified Godunov difference method. S.S. Grigoryan's model with relatively simple equations of state is used as a model of the dynamic behavior of sandy media. The model parameters are based on the results of the plane-wave experiments and the experiments with a modified Kolsky method. The behavior of forces and coefficients of resistance to penetration at different phases of impact interaction is analyzed.
Keywords: penetration; dry sand; resistance force; Grigoryan's model